Online engineering mathematics course: development and implementation of a successful project - Baptista Soares, Filomena (2022)
According to the New UNESCO global survey studying the effect of Covid-19 on higher education (2021) the pandemic has had an impact on higher education systems in terms of access and quality of teaching and learning. Covid-19 has caused the suspension and cancellation of teaching activities and its major impact on teaching and learning is the increase in online education. The Engimath - Mathematics on-line learning model in engineering education - was successfully carried out at the very right moment, as in recent two years there has been a significant increase in demand for a 100% online mathematics course with interactive learning materials and largescale practicing opportunities as well as for a mathematics online assessment model. This project has successfully developed a high-level online course as a basis for offering output-oriented education in engineering mathematics. Some of development stages, that led this project – EngiMath - to an outstanding successful end, will be presented in this paper. These go from the educational needs’ analysis to its implementation and use, even allowing an open and live test.